Exploring dakwah as Muslim cultural element strategy in oral polio vaccination campaign in Nigeria - Ahmad, Gambo Ibrahim; Ahmad, Mohd Khairie; Cheah, Joyce Lynn-Sze (2019)
Oral Polio Vaccination campaign started in Nigeria in 1988 with the sole aim of eradicating poliomyelitis in the country. However, the campaign faces challenge of rejection or non-compliance from mostly Muslim parents of northern Nigeria due to the absence of cultural sensitivity. The study explored the possibility of adopting dakwah a Muslim cultural element as a communication strategy to reach out to the Muslim parents with culturally sensitive oral polio vaccination messages to enhance the acceptance of the campaign. Data was collected through focus group of Muslim parents with eligible children five years and below in states of Kaduna, Kano and Bauchi of northern Nigeria. The findings revealed that the dakwah strategy using learned Islamic scholars that disseminate effective messages with cultural sensitivity and in an interpersonal communication situation will enhance the acceptance of oral polio vaccination among Muslim parents. The study concludes that learned Islamic scholars should be involved fully in the campaign for community mobilisation and sensitisation for the acceptance of the oral polio vaccination.